Ionization differential cross section measurements for H2, D2 and HD at low energies. (23rd October 2015) - Murray, Andrew James
Abstract: In a previous investigation, ionization triple differential cross sections (TDCS) were determined for the simplest neutral molecule H2 over a range of scattering geometries from coplanar to the perpendicular plane, at an incident energy 20 eV above the ionization potential (IP). These data were compared to state of the art theoretical calculations, and significant discrepancies were found that have yet to be resolved. To further this study, new data are presented here for incident energies from 10 to 50 eV above the IP for H2 . These are compared to data for ionization of D2 and HD, to establish if either the nuclear structure or molecular symmetry plays a role in the collision. No significant differences were observed in the measurements from different isotopic species. A comparison with the TDCS from N2 under the same operating conditions is also presented, to contrast differences between these targets.